Two new species of the genus Rhopalopsole (Plecoptera: Leuctridae) from China - Chen, Jing; Wang, Hongliang; Li, Weihai (Zootaxa, 2022)
Two new species of the genus Rhopalopsole (Plecoptera: Leuctridae) are described from China: Rhopalopsole liui Chen, Wang & Li, sp. nov. from from Municipality of Chongqing (former Sichuan Province) and Rhopalopsole yadonga Chen, Wang & Li, sp. nov. from from the Tibet Autonomous Region. The new species are compared to similar congeners in the R. shaanxiensis and R. magnicerca groups, respectively.